1972
DOI: 10.1037/h0032099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of locus of control and type of feedback on the task performance of lower-class black children.

Abstract: Sixty fifth-grade black males from two inner-city elementary schools participated in an experiment designed to examine the effects of variations in locus of controlinternal versus external-on the efficiency of intrinsic and extrinsic types of feedback. The major point of divergence between feedback conditions was whether subjects' knowledge of correctness was acquired by self-discovery of successful task performance (intrinsic reinforcement) or whether the subjects had to depend on the experimenter's personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…(Forness, 1973, remarks that it is doubtful that in the present-day American educational system many students get to that point. In the present synthesis, only one experiment was found, Baron, 1972, to have conditions that appear to correspond to the definition of this category. )…”
mentioning
confidence: 85%
“…(Forness, 1973, remarks that it is doubtful that in the present-day American educational system many students get to that point. In the present synthesis, only one experiment was found, Baron, 1972, to have conditions that appear to correspond to the definition of this category. )…”
mentioning
confidence: 85%
“…We assume that this could be caused by providing feedback just once between two short tests. In many studies the impact of feedback was examined considering several feedback interventions (e.g., Baron, Ganz, 1972;Di Paula, Campbell, 2002;Heslin, Latham, 2004;. It seems probable that the effect of feedback increases by receiving several feedback interventions, for instance across several feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, people with an external LOC (externals) have low expectations of control and attribute failure or success to external sources (e.g., other people, fate, fortune). According to the nature of feedback Baron and Ganz (1972, see also Baron et al, 1974) found that internals achieved a better performance than externals when task-supplied feedback was presented. On the other hand, externals showed a better performance than internals when feedback was given by an experimenter.…”
Section: Core Self-evaluations and Their Impact On Feedbackmentioning
confidence: 99%
“…It was found that kibbutz children who have been raised in a more directive-controlled way (by both parents and educators) develop less of an internal orientation than children who have been raised in an atmosphere which allows more freedom to experiment and possibly to deduce abstract relationships (Baron & Ganz 1972).…”
Section: Discussionmentioning
confidence: 99%